Work Family Conflict On Dual Earner Families: Influence of Economic Pressure, Husband-Wife Interaction, Family Resilience - Agustin, Salsa Bela Frisilia; Sunarti, Euis; Herawati, Tin (TAZKIYA Journal of Psychology, 2025)
Globalization and socio-economic changes have led to an increase in the number of dual-earner families. Jobs that were previously dominated by men are now increasingly being done by women, making the phenomenon of women working commonplace. However, this condition often leads to work-family conflict due to the imbalance of roles at work and home. Family work conflict is an imbalance between work and family that refers to how the relationship between work and family is mutually disrupted. This study analyzes the influence of economic pressure, husband-wife interaction, and family resilience on work conflict in dual-earner families. The research used a quantitative method with an explanatory study design, involving direct interviews with 103 working wives, who were selected by purposive sampling in two places in West Bogor Sub-district, Pasir Jaya Village and Gunung Batu Village. Data were analyzed descriptively using SPSS, while the influence between variables was analyzed using structural equation modeling (SEM). The findings show that economic pressure significantly influences work conflict, where higher pressure increases conflict intensity. In contrast, good husband-wife interaction and high family resilience were shown to reduce work-family conflict effectively. Based on the research, dual-earner families are advised to improve time management, set priorities, and maintain regular communication to strengthen family harmony and resilience.